The Influence of Vitamin D3 Supplementation on LH and FSH Levels in Female Rats (Rattus norvegicus) with Polycystic Ovary Syndrome (PCOS) Model - Gandhari, Anak Agung Sagung Agung Ayuska; Wiyasa, I Wayan Arsana; Hariyati, Suheni Ninik; Baihaqi, Irfani (Asian Journal of Health Research, 2023)
Introduction: Polycystic Ovary Syndrome (PCOS) is a common hormonal disorder in reproductive-aged women, characterized by hormonal imbalances such as Luteinizing Hormone (LH) and Follicle Stimulating Hormone (FSH). This study investigates the impact of Vitamin D3 supplementation on LH and FSH levels in female rats with a PCOS model. Material and Methods: In this laboratory experiment, female rats were induced with testosterone propionate for 28 days. They were divided into three groups: negative control, positive control (testosterone only), and treatment (testosterone + Vitamin D3 supplementation). LH and FSH levels were measured using the enzyme-linked immunosorbent assay method. Results: The results revealed that Vitamin D supplementation significantly reduced FSH levels in the treatment group compared to the positive control, while it increased FSH levels. Regression analysis demonstrated a negative correlation between Vitamin D supplementation and LH levels, as well as a positive correlation with FSH levels. Conclusion: Vitamin D3 supplementation appears to have a regulatory effect on LH and FSH levels in female rats with PCOS. Future research could explore the impact of higher Vitamin D3 doses and conduct further investigations at advanced stages of PCOS. These findings contribute to our understanding of PCOS and potential interventions involving Vitamin D3.